The Spanish version of the stressors in nursing students scale - Sarabia‐Cobo, Carmen; Alconero‐Camarero, Ana Rosa; González‐Gómez, Silvia; Catalán-Piris, María José; del Amo Setien, Francisco; González‐López, José Rafael (Journal of psychiatric and mental health nursing, 2020)
Accessible Summary What is known on the subject? The mental health of health professionals is affected by their own work. Nurses and nursing students face high levels of stress, which results in anxiety, burnout, and depression. There are scales that allow the measurement of specific stress levels of nursing students, especially when they first attend their clinical practices in real settings such as hospitals. What this paper adds to existing knowledge? Our study consists of validating an existing scale (the Stressors in Nursing Students Scale, SINS) that measures these stress levels in Spanish. Stress is an issue for nursing students and is related to the specific stressors they encounter in the process of their professional work and study. What are the implications for practice? The validation and adaptation of this scale to Spain will allow us to adequately assess the stress levels of our students to give them adequate tools for the emotional control of their anxiety and stress. Once we have a reliable and appropriate tool for measuring the factors of greater impact in the generation of stress, we can implement preventive measures which may be very useful for the control of anxiety. Introduction Nursing professionals and students suffer a greater number of stressors with negative health consequences. Aim To translate and test a Spanish version of the Stressors in Nursing Students Scale (SINS‐S), with a cohort of nursing students in Spain. Also, we sought to examine the factor structure of this test and explore the psychometric structure of stress among this population. Method The SINS scale was translated into Spanish and administered to a cohort (n = 398) of male and female Spanish nursing students in the final three years of their nursing program. Data were analyzed using exploratory factor analysis. Results Exploratory factor analysis revealed four factors: “Clinical,” “Financial,” “Confidence,” and “Education.” Discussion There were similarities between the perception of stressors by nursing students in Spain compared with the original version of the SINS from the United Kingdom. Stress is an issue for nursing students and is related to the specific stressors they encounter in the process of their professional work and study.